Tick borne encephalitis (TBE)-vaccination coverage and analysis of variables associated with vaccination, Sweden. Issue 38 (11th September 2015) - Askling, Helena Hervius; Insulander, Mona; Hergens, Maria-Pia; Leval, Amy
Highlights Fifty-three percent of respondents (n = 4307) reported being vaccinated against TBE at least once. Higher income was associated with higher probability of vaccination (OR 2.10 95% CI 1.6–2.73). TBE-incidence in unvaccinated population was comparable with European high endemic areas.